2022
DOI: 10.3390/ma15155456
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Mechanical Properties of Geocell Strips at Low Temperature

Abstract: Geocell is widely used in the treatment of poor roadbed, which can restrain soil laterally and improve the stability of soil. In cold area engineering, a change in temperature can influence the mechanical properties of geocell of different materials. To study the mechanical response of geocell at low temperatures, three types of geocell strips commonly used in engineering, namely the polyethylene (HDPE), polypropylene (PP), and polyester (PET), were studied via the uniaxial tensile test at the ambient temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, only the normal load, geogrid type, coarse grain content, and particle shape are used in the experimental investigation and analysis, and the sample size of each influencing factor is small. Factors such as the load form, surface roughness of reinforced material, soil temperature, number of layers of reinforcement, and spacing of reinforced material also significantly affect the distribution and evolution of the reinforcement influence zone (Bai et al, 2022). In the future, we can continue to expand the investigation of the influencing factors on the detailed mechanism of reinforced soil as well as increase the number of test samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, only the normal load, geogrid type, coarse grain content, and particle shape are used in the experimental investigation and analysis, and the sample size of each influencing factor is small. Factors such as the load form, surface roughness of reinforced material, soil temperature, number of layers of reinforcement, and spacing of reinforced material also significantly affect the distribution and evolution of the reinforcement influence zone (Bai et al, 2022). In the future, we can continue to expand the investigation of the influencing factors on the detailed mechanism of reinforced soil as well as increase the number of test samples.…”
Section: Discussionmentioning
confidence: 99%
“…The geogrid parameter includes geogrid material, geogrid planar structure, geogrid filling rate, rib width and rib width of geogrid. Two main materials are used in geogrids: HDPE 31 and PLA. 32,33 Table 1 presents their material properties while Figure 2 shows their corresponding stress-strain relationship.…”
Section: Experimental Equipments and Materialsmentioning
confidence: 99%
“…The tests indicated that the elongation of the HDPE strip was sensitive to the specimen shape, and the effect of the welding junction on the HDPE strip cannot be ignored. Bai [31] discussed the effect of low temperatures on the mechanical properties of geocell strips made from high-density polyethylene (HDPE), polypropylene (PP), and polyester (PET). The results revealed that the tensile performance of the PET geocell strip is superior to that of the PP and HDPE geocell strips.…”
Section: Geocell Heightmentioning
confidence: 99%